2011
DOI: 10.1007/s12035-011-8181-5
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of Nrf2/ARE Pathway by Food Polyphenols: A Nutritional Neuroprotective Strategy for Cognitive and Neurodegenerative Disorders

Abstract: In recent years, there has been a growing interest, supported by a large number of experimental and epidemi-ological studies, for the beneficial effects of some phenolic substances, contained in commonly used spices and herbs, in preventing various age-related pathologic conditions, ranging from cancer to neurodegenerative diseases. Although the exact mechanisms by which polyphenols promote these effects remain to be elucidated, several reports have shown their ability to stimulate a general xenobiotic respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
219
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(230 citation statements)
references
References 121 publications
5
219
1
5
Order By: Relevance
“…13,14) It has been reported that several plant-derived polyphenolic compounds can exert neuroprotective action through the regulation of HO-1 expression. 44) Keeping this in consideration, the influence of this flavonoid on HO-1 expression was investigated in the H 2 O 2 -treated cells in order to further understand the molecular mechanism(s) underlying its neuroprotective activity. Luteolin caused a marked, time-dependent induction of HO-1 expression (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…13,14) It has been reported that several plant-derived polyphenolic compounds can exert neuroprotective action through the regulation of HO-1 expression. 44) Keeping this in consideration, the influence of this flavonoid on HO-1 expression was investigated in the H 2 O 2 -treated cells in order to further understand the molecular mechanism(s) underlying its neuroprotective activity. Luteolin caused a marked, time-dependent induction of HO-1 expression (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…20 Several lines of evidences have suggested that the induction of Nrf2-regulated phase II enzymes, including HO-1, NQO1, and GCLM, etc, had strongly protective effects against oxidative damage and neuronal death. 18,21 In addition, it was reported that GCLM knockout decreased the life span of SOD1-G93A mice by 55%, which was related to the reduction of GSH. 22 To better understand the role of Nrf2 in ALS, we examined the expression of several phase II enzymes in different tissues, including lumbar spinal cord and motor cortex, of Nrf2 þ / þ and Nrf2 À / À SOD1-G93A mice (Figure 4).…”
Section: Effect Of Nrf2 Knockout On Als Mice Y Guo Et Almentioning
confidence: 99%
“…Another requirement is that the compound should also generate a more stable, and therefore less injurious, intermediate molecule upon reaction with a ROS in order to be considered as a good antioxidant [4]. With the recent findings, these definitions should be broadened to encompass also agents that are capable of sequestering transition metal ions (chelation activity), inhibi-tion of enzymes involved in ROS production and induction of endogenous defense mechanisms such as antioxidant enzymes [18].Large scale epidemiologic cohort studies in different populations have provided evidence that consumption of dietary antioxidants is associated with reduced risks of heart diseases and neurodegeneration [19,20]. Although a number of interventional trials have failed to prove the usefulness of antioxidants for disease management, the use of disease specific, target-directed antioxidants in carefully chosen patients with higher levels of oxidative stress may prove useful in management of certain diseases [14,21,22].…”
mentioning
confidence: 99%